The relationship between cortisol responses to laboratory stress and cortisol profiles in daily life - Kidd, Tara (Elsevier Science B.V, 2014)
Relationships between cortisol responses to laboratory stress and cortisol output over the day have not been studied extensively. We tested associations between cortisol responses to a set of laboratory challenges (colour/word interference and mirror tracing) and three aspects of cortisol output over the day, namely total area under the curve (AUC(day)), the cortisol awakening response (CAR) and the slope of cortisol decline over the day. Participants were 466 men and women aged 54–76 years. We found that cortisol responses to laboratory stress were positively associated with cortisol AUC(day) independently of sex, age, socioeconomic status, smoking, body mass index, and time of laboratory testing (B = 0.212, 95% C.I. 0.143–0.282, p < 0.001). No associations between laboratory responses and the CAR or cortisol slope were observed. The laboratory–field association was not moderated by demographic or psychosocial factors. The study provides evidence for the ecological validity of acute laboratory stress testing.